2015
DOI: 10.17507/jltr.0604.06
|View full text |Cite
|
Sign up to set email alerts
|

Examining the Effectiveness of Group Counseling in Reducing Anxiety for Jordanian EFL Learners

Abstract: Abstract-This study aimed at examining the effectiveness of Rational Emotive Behavior Therapy (REBT) as used in group counseling to reduce the level of anxiety for Jordanian learners of English as a foreign language. The study sample consisted of 32 male and female students at Ajloun National University. The students were all at the undergraduate level and have received the highest anxiety scores on the foreign language anxiety scale. The students were randomly divided into two groups; an experimental group an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 16 publications
0
4
0
Order By: Relevance
“…Our review further found learner-internal features of FLAR interventions. Five studies used performance such as drama ( Sağlamel and Kayaoğlu, 2013 ; Galante, 2018 ; Uştuk and Aydın, 2018 ; Kwiecień-Niedziela et al, 2020 ) or digital storytelling ( Liu et al, 2018 ), five involved strategies ( Alrabai, 2015 ; Mostafavi and Vahdany, 2016 ; He, 2017 ; Tsiriotakis et al, 2017 ; Bielak, 2018 ), four interventions used counseling and training ( Abood and Abu-Melhim, 2015 ; Kralova et al, 2017 , 2018 ; Toyama and Yamazaki, 2019 ), and four used mood boosters such as meditation ( Scida and Jones, 2017 ), music ( Shimbo, 2008 ), gaming ( Wei et al, 2018 ), and web-based L2 exercises ( Bashori et al, 2020 ).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Our review further found learner-internal features of FLAR interventions. Five studies used performance such as drama ( Sağlamel and Kayaoğlu, 2013 ; Galante, 2018 ; Uştuk and Aydın, 2018 ; Kwiecień-Niedziela et al, 2020 ) or digital storytelling ( Liu et al, 2018 ), five involved strategies ( Alrabai, 2015 ; Mostafavi and Vahdany, 2016 ; He, 2017 ; Tsiriotakis et al, 2017 ; Bielak, 2018 ), four interventions used counseling and training ( Abood and Abu-Melhim, 2015 ; Kralova et al, 2017 , 2018 ; Toyama and Yamazaki, 2019 ), and four used mood boosters such as meditation ( Scida and Jones, 2017 ), music ( Shimbo, 2008 ), gaming ( Wei et al, 2018 ), and web-based L2 exercises ( Bashori et al, 2020 ).…”
Section: Resultsmentioning
confidence: 99%
“…In fact, they are designed to improve student–student interactions through peer feedback and teacher-student interaction through debriefing and feedback. Applying rational emotive therapy combined with positive self-talk, two studies ( Abood and Abu-Melhim, 2015 ; Toyama and Yamazaki, 2019 ) reported successful decrease in FLA.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The results obtained from the T-test analysis indicate that there is not a statistically significant disparity in communication apprehension levels between female and male pupils. A study conducted by Abood and Abu-Melhim (2015) investigated the efficacy of Rational Emotive Behavior Therapy (REBT) in the context of group therapy for Jordanian individuals learning English as a foreign language, with the aim of reducing anxiety levels. The results indicate that there is no discernible disparity between genders in terms of communication apprehension, and furthermore, it is possible to mitigate communication apprehension.…”
Section: Literature Studymentioning
confidence: 99%
“…• Rational Emotive Behavior Therapy (REBT) should be used in group counseling to reduce the level of anxiety for students learning English as a foreign language based on the effectiveness of this method exemplified in various studies (Abood & Abu-Melhim, 2015a), for example.…”
Section: Recommendationsmentioning
confidence: 99%